Model Problem Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik - Hadis, Emy Narti; Mahmud, Gamar (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This research aims to determine the application of the Problem-Based Learning learning model to improve the learning outcomes of class XI PLF 1 SMA N 1 Ternate students on vector material. This type of research is Collaborative Class Action Research (PTK). The subjects in this research were students in class XI PLF 1 SMA N 1 Ternate for the 2023/2024 academic year, totalling 28 students. The data collection instrument used in this research was a physics learning outcomes test, analyzed using descriptive statistics. This research was carried out in two cycles. Each cycle stage consists of action planning, implementation, observation, and reflection. The research results show that the percentage of student learning outcomes has increased in each cycle. In cycle I, the posttest results showed an average percentage value of 65.36% and a completion percentage of 64.29%. Meanwhile, in cycle II, the posttest results showed an average percentage value of 77.39% and a completion percentage of 85.71%. Applying the Problem-Based Learning learning model can improve the learning outcomes of class XI PLF 1 SMA N 1 Ternate students on vector material. Keywords: Problem Based Learning, Learning Outcomes, Classroom Action Research